Blindness in Right Eyes after Enema: A Case of Klebsiella pneumoniae-Related Invasive Liver Abscess Syndrome with Endophthalmitis-Caused Blindness as the First Symptom - Qi Jin; Xinrui Zhang; Huifen Yang; Bo Zhao; Yubao Wang (Case Reports in Medicine)
We report a case of Klebsiella pneumoniae invasive liver abscess syndrome (KPILAS) with endophthalmitis-caused blindness as the first symptom after enema. The patient had diabetes, and his blood glucose was poorly controlled. She developed hematuria after four enemas for cosmetic purposes and later became blind. The eye discharge was cultured, which revealed a Klebsiella pneumoniae infection. B ultrasound did not show liver lesions, but computed tomography exhibited abscesses in the right lobe of the liver. Magnetic resonance imaging of the head indicated abscesses. These confirmed the diagnosis of invasive liver abscess syndrome. The patient was given ophthalmic and systemic anti-infection treatments, and her condition was effectively controlled. Unfortunately, the diseased eye still needed to be removed. This case underlines the necessity of avoiding unnecessary risky procedures (such as enemas) in vulnerable populations, the importance of early detection of invasive liver abscess syndrome, and the advantage of computed tomography in detecting liver abscesses.